2021
DOI: 10.1097/md.0000000000025726
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Xihuang pill for gastric cancer

Abstract: Background: Xihuang pill has been widely applied as a promising adjunctive drug for gastric cance. However, the exact effects and safety of Xihuang pill have yet to be systematically investigated. We aimed to summarize the effificacy and safety of Xihuang pill for the treatment of advanced GC through the meta-analysis, in order to provide scientific reference for the design of future clinical trials. Methods: The protocol followed Preferred Reporting Items for Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We identified 78 studies on clinical aspects of Xihuang pills/capsules in treating cancer, including 11 specific types of cancer and multiple types of cancer. Twenty-five studies reported in treating breast cancer (32%) [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ] ( Table 2 ), 14 lung cancer (17.9%) [ 6 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ] ( Table 3 ), 11 cervical cancer (14.1%) [ 5 , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ] ( Table 4 ), 6 esophagus cancer (7.6%) [ [60] , [61] , [62] , [63] , [64] , [65] ] ( Table 5 ), 5 liver cancer (6.4%) [8,66 = 69], ( Table 6 ), 3 pancreatic cancer (3.8%) [ [66] , [67] , [68] ] ( ...…”
Section: Resultsmentioning
confidence: 99%
“…We identified 78 studies on clinical aspects of Xihuang pills/capsules in treating cancer, including 11 specific types of cancer and multiple types of cancer. Twenty-five studies reported in treating breast cancer (32%) [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ] ( Table 2 ), 14 lung cancer (17.9%) [ 6 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ] ( Table 3 ), 11 cervical cancer (14.1%) [ 5 , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ] ( Table 4 ), 6 esophagus cancer (7.6%) [ [60] , [61] , [62] , [63] , [64] , [65] ] ( Table 5 ), 5 liver cancer (6.4%) [8,66 = 69], ( Table 6 ), 3 pancreatic cancer (3.8%) [ [66] , [67] , [68] ] ( ...…”
Section: Resultsmentioning
confidence: 99%
“…XHP has therapeutic effects on diverse tumors. It is widely used as a supplementary drug in the treatment of a variety of malignant tumors in China, such as pancreatic cancer [ 6 ], lung cancer [ 27 ], gastric cancer [ 28 ], and breast cancer [ 29 ]. However, the underlying mechanisms of XHP treating cancers remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…(Zhang et al, 2021b). It has been widely used in the treatment of a variety of malignant tumors in clinics in China, including breast cancer, lung cancer, gastric cancer, and other malignant tumors (Wang et al, 2020a;Wang et al, 2021a;Ge et al, 2022). In mice with Lewis lung cancer, Cao et al investigated the anti-lung cancer impact of XHW coupled with anlotinib (LLC).…”
Section: Compound Formulation Of Tcmmentioning
confidence: 99%
“…Studies indicate links between dysbiosis or disturbance in the microbiome and diseases that not only affect the gut but also organs like the lung, thyroid, brain, cardiac, immune system, etc. ( Tang et al., 2019 ; Hufnagl et al., 2020 ; Knezevic et al., 2020 ; Rutsch et al., 2020 ; Wang et al., 2022a ). The crosstalk between the gut microbiome and distal organs is being increasingly recognized, and host-microbiome interactions are being delineated piece by piece.…”
Section: Close Relationship: Gm and Nsclcmentioning
confidence: 99%